From novice to navigator: Students’ academic help-seeking behaviour, readiness, and perceived usefulness of ChatGPT in learning - Donnie, Adams; Chuah, Kee Man; Edward, Devadason; Muhammad Shamshinor, Abdul Azzis (Springer Nature, 2023)
The emergence of chatbots and language models, such as ChatGPT has the potential to aid university students’ learning experiences. However, despite its potential, ChatGPT is relatively new. There are limited studies that have investigated its usage readiness, and perceived usefulness among students for academic purposes. This study investigated university students’ academic help-seeking behaviour, with a particular focus on their readiness, and perceived usefulness in using ChatGPT for academic purposes. The study employed a sequential explanatory mixed-method research design. Data were gathered from a total of 373 students from a public university in Malaysia. SPSS software version 27 was used to determine the reliability of the research instrument, and descriptive statistics was used to assess the students’ readiness, and perceived usefulness of ChatGPT for academic purposes. Responses in the open-ended questions were analysed using a four-step approach with ATLAS.ti 22. Research data from both the quantitative and qualitative methods were integrated. Findings indicated that students have the proficiency, willingness, and the requisite technological infrastructure to use ChatGPT, with a large majority attesting to its ability to augment their learning experience. The findings also showed students’ positive perception of ChatGPT’s usefulness in facilitating task and assignment completions, and its resourcefulness in locating learning materials. The results of this study provide practical implications for university policies, and instructor adoption practices on the utilisation of ChatGPT, and other AI technologies, in academic settings.